Assessing impacts of simulated oil spills on the Northeast Arctic cod fishery. (January 2018) - Carroll, JoLynn; Vikebø, Frode; Howell, Daniel; Broch, Ole Jacob; Nepstad, Raymond; Augustine, Starrlight; Skeie, Geir Morten; Bast, Radovan; Juselius, Jonas
Abstract: We simulate oil spills of 1500 and 4500 m 3 /day lasting 14, 45, and 90 days in the spawning grounds of the commercial fish species, Northeast Arctic cod. Modeling the life history of individual fish eggs and larvae, we predict deviations from the historical pattern of recruitment to the adult population due to toxic oil exposures. Reductions in survival for pelagic stages of cod were 0–10%, up to a maximum of 43%. These reductions resulted in a decrease in adult cod biomass of < 3% for most scenarios, up to a maximum of 12%. In all simulations, the adult population remained at full reproductive potential with a sufficient number of juveniles surviving to replenish the population. The diverse age distribution helps protect the adult cod population from reductions in a single year's recruitment after a major oil spill. These results provide insights to assist in managing oil spill impacts on fisheries. Graphical abstract: Highlights: We perform simulations of the toxic effects of oil spills on Northeast Arctic cod. Spill scenarios result in reduced survival for pelagic stages of cod between 0 and 43%. The reproductive health of the adult population is maintained in all scenarios. Moderate action by fisheries managers can mitigate impacts on the fisheries.